Physical Datarepresentation in a Multiprocessor Database Machine - Staunstrup, Jørgen; Jespersen, Jens Ove; Johansen, Ole V. (DAIMI Report Series, 1983)
By using a multiprocessor to implement the lowest level of a relational database we want to achieve fast execution of database operations such as join, find, and update. But the potential speed improvements provided by a multiprocessor can only be achieved if one can construct algorithms and corresponding physical data representations that can utilize the potential. By choosing a particular representation, the grid file, and analyzing its behaviour, we want to point out the difficulties encountered in trying to achieve speed improvements from a multiprocessor.